2019
DOI: 10.1002/ejhf.1604
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound‐guided treatment in ambulatory patients with heart failure: a randomized controlled clinical trial (LUS‐HF study)

Abstract: AimsLung ultrasound (LUS) is a useful tool with which to assess subclinical pulmonary congestion and to stratify the prognosis of patients with heart failure (HF). The aim of this study was to evaluate whether an LUS‐guided follow‐up protocol improves the outcomes of patients with HF.Methods and resultsIn this single‐blind clinical trial, 123 patients admitted for HF were randomized to either a standard follow‐up (n = 62, control group) or a LUS‐guided follow‐up (n = 61, LUS group). The primary endpoint was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
188
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(199 citation statements)
references
References 30 publications
2
188
0
9
Order By: Relevance
“…This is a post-hoc analysis of the LUS-HF trial. 11 Briefly, this was a single-centre, single-blind, randomized clinical trial evaluating whether a LUS-guided follow-up protocol improves the outcomes in patients with HF. Patients were required to be aged ≥18 years and to have been hospitalized for ADHF defined by shortness of breath, pulmonary congestion on X-ray, and high N terminal pro brain natriuretic peptide (NT-proBNP) values in the first 24 h of admission (cutoff values: 450 ng/L in patients aged <50 years; >900 ng/L in patients aged 50-75 years; >1800 ng/L in patients aged >75 years).…”
Section: Methodsmentioning
confidence: 99%
“…This is a post-hoc analysis of the LUS-HF trial. 11 Briefly, this was a single-centre, single-blind, randomized clinical trial evaluating whether a LUS-guided follow-up protocol improves the outcomes in patients with HF. Patients were required to be aged ≥18 years and to have been hospitalized for ADHF defined by shortness of breath, pulmonary congestion on X-ray, and high N terminal pro brain natriuretic peptide (NT-proBNP) values in the first 24 h of admission (cutoff values: 450 ng/L in patients aged <50 years; >900 ng/L in patients aged 50-75 years; >1800 ng/L in patients aged >75 years).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of ≥ 15 B-lines correlates with NT-proBNP > 1000 pg/ml and E/e′ ratio > 15 [45]. This may even lead to improved patient outcomes as demonstrated in a small randomized trial, LUS-HF, which found that recently discharged HF patients who were assessed using LUS during follow-up were associated with a significantly reduced rate of HF re-admissions [46]. Clinicians should thus integrate these newer technologies with physical examination for a more accurate judgement of fluid status.…”
Section: Excessive Intravenous Fluid and Under-diuresismentioning
confidence: 95%
“…Три стадии легочного застоя при хронической сердечной недостаточности "Сухое" легкое "Мокрое" при нагрузке легкое "Мокрое" в покое легкое Легкое в покое "сухое" "сухое" "мокрое" Легкое при нагрузке "сухое" "мокрое" очень "мокрое" И, наконец, наиболее значимой на сегодняшний день работой, демонстрирующей перспективность использования стратегии оптимизации диуретической терапии пациентов с ХСН под контролем УЗИ легких, является рандомизированное исследование LUS-HF [31,32]. В исследование были включены 123 пациента, поступившие в стационар с декомпенсацией ХСН.…”
Section: таблицаunclassified